WAR CRIMES FROM THE PERSPECTIVE OF ISLAMIC LAW AND INTERNATIONAL LAW - Simatupang, Rajarif Syah Akbar; Ritonga, Arifin Said; Sihombing, Daulat; Lubis, Pangiutan Tondi; Mansar, Adi (Proceeding International Seminar of Islamic Studies, 2024)
War is the highest form of conflict between humans that involves the use of weapons. War is a human tragedy that causes death and priceless losses. War always gives rise to various economic, political and social consequences that degrade human values. As a form of awareness of the consequences and consequences of war, it was agreed to establish International Humanitarian Law. In line with the Preamble to the 1945 Constitution of the Republic of Indonesia, Indonesia is one of the countries that has ratified the international convention on International Humanitarian Law. Conceptually, Islamic law, national law and international law regulate the conditions of war. However, in practice, the terms of the war were not implemented consistently and consistently until the war turned into a war crime. The aim of this research is, firstly, to examine and analyze Islamic law, national law and international law regarding war crimes, secondly to examine and analyze forms of efforts to enforce national law and international law regarding war crimes. The research method uses a type of normative research which places law as a system of norms, the subject of the study is conceptualized in the norms that apply in society, this type of research is taken through literature, which means legal research by examining library materials or documents.